Analysis of transactivation capability and conformation of p53 temperature-dependent mutants and their reactivation by amifostine in yeast - Nikulenkov Grochová, Diana; Vaňková, J; Damborský, Jiří; Ravčuková, Barbora; Šmarda, Jan; Vojtěšek, Bořivoj; Šmardová, Jana (Oncogene, 2008)
The p53 gene is often mutated during cancer development. Frequency and functional consequences of these mutations vary in different tumor types. We analysed conformation and temperature dependency of 23 partially inactivating temperature-dependent (td) p53 mutants derived from various human tumors in yeast. We found considerable differences in transactivation capabilities and discriminative character of various p53 mutants. No correlations in transactivation rates and conformations of the td p53 proteins were detected. Amifostine-induced p53 reactivation occurred only in 13 of 23 td mutants, and this effect was temperature dependent and responsive element specific. The most of the p53 mutations (10/13) reactivated by amifostine were located in the part of the p53 gene coding for hydrophobic beta-sandwich structure of the DNA-binding domain.
Keywords: Tumor Suppressor Protein p53; Amifostine; Protein Conformation; Saccharomyces cerevisiae Proteins; Saccharomyces cerevisiae - proteiny; Radiation-Protective Agents; Amino Acid Substitution; Transcriptional Activation; lidé; nádorový supresorový protein p53; aktivace transkripce; amifostin; radioprotektivní látky; financování organizované; substituce aminokyselin; Temperature; Humans; Financing, Organized; konformace proteinů; teplota